A case study of stand-alone hybrid power systems for a data center using HOMER and DIgSILENT. (March 2023) - Kim, Beopsoo; Kim, Insu
Abstract: The number of mega data centers is steadily expanding as the cloud business expands. The data center consumes heavy electrical power because of their structural and equipment characteristics (e.g., workstations and cooling equipment). The mega data center becomes a microgrid (e.g., islanding operation). So, a lot of researchers have proposed the architecture design of a green energy data center to solve the heavy energy consumption problem and to reduce the emission release. For example, the goal of a green energy data center is to maximize energy efficiency while reducing environmental impacts (e.g., the reduction of greenhouse gases). So, the goal of this study is to design the most effective power system for a stand-alone hybrid green data center at the aspects of energy savings and the reliable operation. The ideal architecture of a stand-alone data center powered by renewable energy is initially designed by the HOMER program. Then, the steady-state and transient responses of a data center that functions as an island microgrid using DIgSILENT© Power Factory are examined.